Observation study of using a small dose of rituximab treatment for thyroid-associated ophthalmopathy in seven Chinese patients: One pilot study - Wang, Yueyue; Hu, Hao; Chen, Lu; Zhang, Haitao; Yang, Tao; Xu, Xiaoquan; Chen, Huanhuan (Frontiers in Endocrinology, 2023)
Objective: To report the efficacy, long-term safety, and tolerability of using a small dose (125 mg/m2 weekly for 4 weeks) of rituximab to treat Chinese patients with thyroid-associated ophthalmopathy (TAO). Methods: Seven patients with active moderate-to-severe TAO were prospectively recruited in this study. A small dose of rituximab (125mg/m2 body surface area) was given weekly with a duration of four weeks. Thyroid function, thyrotropin receptor antibody (TRAb), B cell and T cell subsets, ophthalmological examination, magnetic resonance imaging derived parameters, and adverse reactions were recorded at each visit. Results: Seven patients were followed for an average of 224 weeks. B-cell depletion was observed in all patients following rituximab infusion. The clinical activity score (CAS) decreased from 4.86 ± 0.69 to 3.00 ± 0.82 at 5 weeks after treatment (P = 0.033) and remained significantly lower than baseline values at the end of follow-up (P = 0.001). Compared to baseline values, significant decreases in exophthalmos of the right eye, the thickness of extraocular muscles with maximum signal intensity, and the highest signal intensity ratio (SIR) of extraocular muscle to ipsilateral temporal muscle values were observed at the last follow-up (all P < 0.05). Disease progressions or recurrences were not observed during follow-up. Only mild fatigue was observed after the first infusion as a side effect (n = 1). Conclusion: Small dose of rituximab may be a promising option with adequate safety, tolerability, and long-term efficacy for patients with active moderate-to-severe TAO.